New generation of materials based on lesscommon elements - D. V. Drobot; P. A. Shcheglov; E. E. Nikishina; E. N. Lebedeva; G. V. Zimina; I. N. Smirnova; V. V. Fomichev (Тонкие химические технологии)
The overview discloses the results of development of synthetic methods and investigation of physico-chemical properties (structure, thermal, thermodynamic, electrophysical and catalytic characteristics) of a wide range of materials based on less-common elements. These involve materials prospective for application in computer memory, superionic conductors of NASICON-type phases, substrates for HTSC-films of various composition. The results of directed search and chemical design of precursors (soft chemistry routs) for fabrication of ferroelectrics, alloys and mixtures based on refractory metals of V-VII Groups in nano-dispersed state, solid solutions based on corresponding oxides and complex oxide phases are concerned